Farmacovigilância em fitoterapia: plantas empregadas para fins medicinais por usuários de serviços de hepatologia e nefrologia no município de São Luís, Maranhão, Brasil - SILVA, Orlene Nascimento da (2019)
The use of plant species for therapeutic purposes without validation studies may contribute to the risk of toxic reactions, with emphasis on hepatic and renal damage, due to the physiological processes of metabolism and excretion of substances. In this sense, due to the difficulty of identifying adverse events to the use of plants for medical purposes, both by the user and by the health professional, the ethnopharmacological studies have provided important subsidies, enabling the evaluation of the therapeutic resources employed by the population. Thus, this study aims to perform an ethnopharmacological study for the identification of plant species used by users of the public service of nephrology and hepatology in the city of São Luís, Maranhão, Brazil; aiming to effectively contribute in the rational use of plants for medicinal purposes and Pharmacovigilance actions. We interviewed 84 individuals for the hepatology service and 145 individuals for the nephrology service in public health care centers of Primary Health Care, with a prevalence of 75% and 60% of the use of plants for medical purposes by users of hepatology and nephrology services, respectively. In relation to the source of information about the use of plants for medicinal purposes by the selected users in the services of hepatology and nephrology, information obtained from family members predominated (79,76% and 73,10%), as regards the place of purchase the quintal / home garden (50% and 50,56%) predominated, using decoction (30,25% and 57,15%) as the main form of preparation, with satisfaction level with the preparations obtained from plants predominantly good (62,13% and 63,34%) or excellent (37,87% and 35,55%), respectively. Regarding the frequency of use of the preparations, the users of the hepatology service use one (01) time a day, while those the interviewees by the nephrology services use more than 3 times a day, both referring to using the preparation for the duration of the symptoms. The most frequently used therapeutic categories cited by the respondents of the hepatology service were evidenced predominance of indication of plant species to treat diseases of the digestive system, followed by diseases of the nervous system and diseases of the genitourinary system. In the users of nephrology services, plants for diseases of the digestive system, followed by diseases of the nervous system and symptoms, signs and abnormal clinical and laboratory findings, not elsewhere classified; having as the most cited plant species: Lippia alba (Mill) N. E. Brown. (erva cidreira), indicated for soothing and Rhamnus purshiana DC. (cáscara sagrada) for constipation, already by the users of the nephrology service were: Lippia alba (Mill) N. E. Brown. (erva cidreira), indicated for soothing and Plectranthus barbatus Andrews (boldo) for colic treatment. Most respondents do not recognize dangers in their use popular practice. However, users refer to the use of some plants for other therapeutic purposes, although with hepatotoxic and nephrotoxic properties well described in the literature, and may lead to worsening in the health of the main complaint that condition them to seek such services. Therefore, the confirmation of the extensive use for therapeutic purposes of plant species requires effective action of the inspection bodies, with a commitment of effective action in Pharmacovigilance in Phytotherapy, with emphasis on educational actions alerting the population to the risks and dangers associated with empirical use.